Pelaku Dan Korban Bullying Siswa Sekolah Dasar di Wilayah Kabupaten Tegal - Susi Muryani; Nurhakim Yudhi Wibowo; Yessy Pramita Widodo; Ratna Widhiastuti (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2023)
Introduction: Bullying is an action that can affect students during the learning process at school at various age levels. Bullying or bullying involves an imbalance of power between the perpetrator and the victim which is manifested by aggressive actions. Purpose: The aim of the research is to determine the role of the perpetrator or victim in bullying. Method: Descriptive analysis research design in the Tegal Regency area. The sample used was 97 students. The research tool for measuring bullying uses the peer relations questionnaire (PRQ). Result: The results of the research showed that the number of perpetrators was 67 students and the victims were 30 students. Between the perpetrator and the victim, most bullying roles are dominated by behavioral roles.